(untitled) (Papeles, 2023)
The article addresses, in historical perspective, social policies and State models. It recovers various research findings derived from training paths and reveals the specific contribution of Social Work in the implementation of an iconic policy such as the Universal Child Allowance, institutionalized in October 2009 through Decree 1602/09. The tour allows to identify the tensions themselves happened from the moment of institutionalization and the nuances that it takes once it is launched, it also analyzes how professionals in the field of health and education of the city of Santa Fe, dispute in microsocial spaces the meaning of it. In this way, the controversies that emerge in the institutions where they work are identified, opposing tendencies between those who consider it as a right and others who dispose of it as an assistance or help. These conceptions have implications, not only in the accessibility and permanence of the recipients, but also in the organizations responsible for certifying the required conditionalities. Finally, we will explain the contribution that professionals make to this policy, without their role being formally assigned in the design phase.